POLA ASUH DALAM KELUARGA POLIGAMI TERHADAP PERKEMBANGAN SOSIAL-EMOSIONAL ANAK PERSPEKTIF PSIKOLOGI HUKUM - Dhea Annisa Putri; Tri Eka Putra Mukhtarivansyah Waruwu (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
This study examines the influence of parenting patterns in polygamous families on children's socio-emotional development in Sidomulyo Village, Stabat District, from the perspective of family legal psychology. The research employed an empirical juridical method with a qualitative case-study approach, integrating normative analysis with field data obtained through in-depth interviews and observations. The findings reveal a gap between legal norms and parenting practices in polygamous families, particularly regarding limited paternal involvement and the lack of justice within family relations. Parenting was predominantly carried out by mothers through a democratic approach emphasizing emotional closeness and communication, yet within an imbalanced family structure. These conditions affected children's socio-emotional development, including reduced self-confidence, emotional instability, social interaction difficulties, relational conflicts, and alienation from the father figure. The study highlights that parenting quality, family emotional stability, and balanced parental roles are crucial factors in supporting optimal child development. Therefore, integrating psychological perspectives into family law is essential to strengthen more comprehensive and responsive child protection policies.